Cultivating Intrinsic Motivation through Uswatun Hasanah Leadership and Satlogi Santri Core Values in Islamic Pedagogy - Nanang Qosim; Abu Siri (CV. Bimbingan Belajar Assyfa, 2025)
Modern Islamic pedagogy requires seamlessly integrating classical spiritual principles with institutional culture to address contemporary educational challenges. This study aims to analyze the implementation of Uswatun Hasanah (exemplary) leadership integrated with the local wisdom of Satlogi Santri to strengthen students' intrinsic learning motivation at the Zainul Hasan Genggong Islamic Boarding School, Probolinggo. Employing a qualitative approach, data were comprehensively gathered through in-depth interviews, observations, and document analysis involving the Kiai, Ustadz, and santri within the pesantren ecosystem. The findings reveal that Uswatun Hasanah leadership, which prioritizes moral, spiritual, and ethical exemplification, significantly boosts students' learning enthusiasm. Furthermore, the six core principles of Satlogi Santri—politeness, steadfastness (istiqamah), advice, Taqwallah, Ridhollah, and Ikhlas Lillahi Ta'ala—effectively function as institutional corporate values that construct a disciplined and spiritually oriented learning ecosystem. The authentic exemplary behavior of educators in worship and patience catalyzes the students' intrinsic motivation, shifting their learning perspective from a mere academic obligation to a profound act of devotion. In conclusion, integrating traditional pesantren values into the leadership and pedagogical framework successfully builds sustainable, worship-oriented learning motivation, offering a robust model for character education and holistic learning management in contemporary Islamic educational institutions.